Evaluation and acceptability of patient-reported outcome measures in women following pelvic organ prolapse procedures - Rasa Ruseckaite; Randi Jayasinghe; Claire Bavor; Joanne Dean; Oliver Daly; Susannah Ahern (BMC, 2023)
Abstract Background The Australasian Pelvic Floor Procedure Registry (APFPR) captures clinical and surgical data in women undergoing pelvic floor procedures. The inclusion of patient reported outcome measures (PROMs) in the APFPR is a critical activity providing the additional patient perspective of their condition prior to surgery as well as monitoring beyond the usual post-surgical follow-up time. This study aimed to evaluate the acceptability of seven PROMs for women with pelvic organ prolapse (POP) and to determine the most suitable instrument for the APFPR. Methods Semi-structured qualitative interviews were conducted with women with POP (n = 15) and their treating clinicians (n = 11) in Victoria, Australia. Interview topics covered appropriateness, content, and acceptability of seven POP-specific instruments identified through the literature to determine their suitability and acceptability for inclusion in the APFPR. We analysed the interview data using conventional content analysis. Results All study participants agreed that PROMs were needed for the APFPR. Both women and clinicians suggested that some of the instruments were ambiguous, too long and confusing. The Australian Pelvic Floor Questionnaire was accepted widely amongst women and clinicians and recommended for inclusion in the APFPR. All participants agreed it would be appropriate to capture PROMs before surgery, and then followed up post-surgically. Email, phone call or postal mail-out were the preferred options for PROMs data collection. Conclusion Most women and clinicians supported incorporating PROMs in the APFPR. Study participants believed that capturing PROMs would have potential use in individual care and improve outcomes of women with POP.